Kajian Teologis Tentang Implementasi Pemuridan Dalam Gereja - Malik, Malik; Gulo, Yarnida (Views : Jurnal Teologi dan Biblika, 2025)
Discipleship is the Great command of the Lord Jesus specifically for believers to make all nations disciples of Christ. This is in accordance with Jesus' command to the disciples as written in Matthew 28:19. The essential thing for disciples is to make others disciples of Christ, but in reality in the church today, there are churches that have not been involved in this discipleship. This study aims to find out how the implementation of discipleship in the church is through a theological study. The method used is a qualitative method. With a literature study approach, through relevant books and article manuscripts related to the topic of this discussion. As a result of this study, the church needs to grow in quality, the church needs to grow in quantity, the church needs to grow organically. The conclusion of the study is that the disciples in carrying out the Great Commission by preaching the Gospel of salvation through the path of discipleship, shepherding the souls of God's choice well and responsibly.